PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS CANVA UNTUK MATERI SUKU KATA PADA PELAJARAN BAHASA INDONESIA KELAS 1 SDN KADEMANGAN 2 PROBOLINGGO - Diana Agustin Susilowati; Ribut Prastiwi Riwijayanti; Faridahtul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted because of the low ability of students in understanding the syllable material of Indonesian language lessons and the lack of utilization of learning media. The purpose of this study was to produce a product in the form of Audio Visual Media in the Indonesian language subject for class I SDN Kademangan 2 Probolinggo. This study uses the research and development method (Research & Development). The development model used in this study is the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the results of research and development, it shows a percentage of 94% by learning material experts, by learning media experts 90%, Indonesian language learning practitioners with a percentage of 95%, and the results of the recapitulation of student responses with a percentage of 92%. The results concluded that the development of audio visual learning media based on the Canva application on the Syllable material in Indonesian language lessons developed using the ADDIE model is suitable for use as a learning medium.